2018
DOI: 10.1080/11038128.2018.1495762
|View full text |Cite
|
Sign up to set email alerts
|

Everyday activities outside the home are a struggle: Narratives from two persons with acquired brain injury

Abstract: Background: Participation restriction is a common consequence after acquired brain injury (ABI). Aim: To explore and identify problematic situations in everyday activities outside the home for persons with acquired brain injury. Material and Method: Two persons of working age with ABI were included. Data were generated through repeated semi-structured interviews and participant observations. Narrative analysis was used to capture ongoing processes related to problematic situations during engagement in everyday… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 40 publications
(64 reference statements)
1
22
0
Order By: Relevance
“…Interestingly, two out of four items representing symbolic value were perceived as low. This might indicate, in line with previous research [16,17] that engagement in socio-cultural occupations becomes restricted, such as occupations with others in public space. The results also showed that all three dimensions of values were of significant importance for somatic health, psychological health and life as a whole.…”
Section: Aspects Of Occupational Valuesupporting
confidence: 86%
See 1 more Smart Citation
“…Interestingly, two out of four items representing symbolic value were perceived as low. This might indicate, in line with previous research [16,17] that engagement in socio-cultural occupations becomes restricted, such as occupations with others in public space. The results also showed that all three dimensions of values were of significant importance for somatic health, psychological health and life as a whole.…”
Section: Aspects Of Occupational Valuesupporting
confidence: 86%
“…Their engagement in occupations becomes more or less limited to activities that need to be performed to function in everyday life [15]. Furthermore, engagement in activities outside the home, such as social and leisure activities, often becomes challenging, and as a result, people with ABI visit fewer places and perform more of their activities at home and alone [15][16][17].…”
mentioning
confidence: 99%
“…Participation commonly include engagement in activities in numerous places. After a stroke, it can be challenging to be engaged in activities in places outside the home [1][2][3][4]. Recent research has found that people with a severe or moderate disability after a stroke visit fewer places, compared to those with good recovery after stroke [5].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, these results indicate the importance of considering places visited for activities outside the home to understand better the extent of participation in different areas of life after stroke, especially for those with severe/moderate disability. With respect to the results and research (Olofsson et al, 2017(Olofsson et al, , 2018, it is suggested that the possibility of facilitating participation can be enhanced by considering places and activities in combination. However, generalisation of the results should be made with caution with respect to the small and non-randomised study sample of working age.…”
Section: Discussionmentioning
confidence: 99%